2019
DOI: 10.17344/acsi.2018.4705
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Degradation of Reactive Blue 21 and Synthetic Textile Effluent by Using Co47.5/C47.5-PVC5 Composite Electrode

Abstract: In this study, cobalt/graphite-polyvinyl chloride (Co 47.5 /C 47.5 -PVC 5 ) composite electrode was fabricated by mechanical alloying technique. The fabricated electrode and graphite rod were used as anode and cathode, respectively, in the decolourisation of aqueous C. I. Reactive Blue 21 (RB21) and synthetic textile effluent, containing a mixture of azo and anthraquinone dyes. The fabricated electrode showed high efficiency in the decolorisation of aqueous RB21 (99.95%) and synthetic textile effluent. This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…According to Shi et al, 22 as an electrode material, C possesses good electrical conductivity, high power density and good cycling stability. In the researchers' previous reported articles, a high percentage decolourization of Reactive Orange 4 39 and Reactive Blue 21 2 (99.12% and 99.95%, respectively) were obtained using graphite/ silver and graphite/cobalt composite electrodes, respectively.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…According to Shi et al, 22 as an electrode material, C possesses good electrical conductivity, high power density and good cycling stability. In the researchers' previous reported articles, a high percentage decolourization of Reactive Orange 4 39 and Reactive Blue 21 2 (99.12% and 99.95%, respectively) were obtained using graphite/ silver and graphite/cobalt composite electrodes, respectively.…”
Section: Introductionmentioning
confidence: 93%
“…Only 60-90% of the dyes used are fixed to textile fibrethe remainder (10-40%) may remain unfixed and thus released into the effluent. 2 This creates a severe water pollution problem which is harmful to human and aquatic life. According to Youseff et al, 3 dyes that absorb and scatter sunlight lead to algae growth.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 The COD of synthetic textile effluent was removed ≥75% using graphite rod anode for 45 min. 22 It was observed that the electrochemical oxidation process has achieved more than 90% removal of COD, BOD, and colour of textile dye using Ag/C composite anode after 100 min. 23 Indirect electrochemical treatment of landfill leachate showed 87% removal of COD using graphite-PVC anode by operating at 15 V applied voltage for 105 min of electrolysis.…”
Section: Introductionmentioning
confidence: 96%